ORGANIZATIONAL FACTORS AND EMPLOYEE BEHAVIORS WITHIN THE PUBLIC SECTOR - Philip Adekanmbi, Foluso; IsiomaUkpere, Wilfred (International Journal of Psychosocial Rehabilitation, 2021)
This paper examines the relationships among organizational factors (organizational culture, commitment, and support) and employee behaviors (organizational citizenship behavior and workplace deviant behavior) within Nigeria’s public sector. The researchers drew the study’s sample from 6 public service ministries within Oyo and Lagos States of Nigeria and adopted a quantitative research approach. The questionnaires were randomly distributed, and out of 300 questionnaires, 287 were useful for analysis. The analysis was conducted using SPSS version 26. The findings indicate that promoting positive organizational culture, commitment, and support is related to organizational citizenship behaviors and deviant behaviors. Additionally, demographics such as age, work experience, gender, religion, marital status, and educational qualification show statistical correlations with the level of organizational citizenship behavior and workplace deviant behavior. Therefore, it is recommended that the government encourage a constructive organizational culture, adequate commitment, and support to promote citizenship behaviors and discourage deviant behaviors in the workplace.